Strategi dan Model Komunikasi Lingkungan Komunitas Makassar Berkebun Dalam Memperkenalkan Konsep Urban Agriculture Di Kota Makassar Sulawesi - Selatan - Febrianto Syam; Zulfiani Zulfiani; Sadhriany Pertiwi Saleh (Al-MUNZIR, 2022)
This article discusses how Makassar Berkebun, an urban farming community in Makassar Sulawesi-Selatan, communicates its environmental message through the qualitative analysis of environmental communication strategies dan models in Introducing the Concept of Urban Agriculture. This article also discusses how the communication strategies used contributed to increasing knowledge, understanding, and community participation in Urban Agriculture and plantation activities in Makassar City. This research is qualitative research that obtained the data from interviews and literature research delivered descriptively. The approach used is the Environmental Communication Science approach and the concept of Urban Agriculture. The results of this research show that there are four types of communication strategies applied by Makassar Berkebun Community to realize the vision and mission of the community, namely; Socialization, Campaign, Education, and Training. This research also shows that the communication model used to analyze the communication strategy applied by Makassar Berkebun Community is a mechanistic and interactional communication model, namely the communication model of David K Berlo (1960) and the communication model of Schramm (1954).Keywords: environmental communication, urban agriculture, Makassar Berkebun Community